STRATEGI GURU DALAM MENGEMBANGKAN KEMAMPUANBERBAHASA RESEPTIF ANAK USIA 4 - 5 TAHUN DI YAYASAN PENDIDIKAN TADIKA BORNEO MEDAN - Awaliyah Yusni Ramadhan Siregar; Masganti; Muhammad Basri (Jurnal Genta Mulia, 2024)
The teacher's strategy for developing the receptive language skills of children aged 4 - 5 years at the Tadika Borneo Education Foundation in Medan is by implementing a chain word game. This research aims to 1) Understand receptive language skills in children aged 4 - 5 years at the Tadika Borneo Education Foundation Medan, 2) Find out what strategies educators use to develop receptive language skills in children aged 4 - 5 years at the Tadika Borneo Education Foundation Medan, 3) Understand the stages in the strategies used by educators to develop the receptive language skills of children aged 4 - 5 years at the Tadika Borneo Education Foundation, Medan. The method used in this research is a qualitative method. The subjects in this research were 11 children aged 4 - 5 years at the Tadika Borneo Education Foundation in Medan. The results of this research show that the receptive or receptive language skills of children aged 4 - 5 years at the Tadika Borneo Education Foundation in Medan have developed as expected with a success percentage of 63%. This is shown by observations and interview results which suggest that chain word games can develop the receptive language of children aged 4 - 5 years and respondents also feel comfortable when the chain word game process is carried out.